Epitaxial growth of complex metal oxides : techniques, properties and applications - Koster, Gertjan, 1971-; Huijben, M.; Rijnders, Guus (Woodhead Publishing series in electronic and optical materials ;, 2015)
The atomic arrangement and subsequent properties of a material are determined by the type and conditions of growth leading to epitaxy, making control of these conditions key to the fabrication of higher quality materials. Epitaxial Growth of Complex Metal Oxides reviews the techniques involved in such processes and highlights recent developments in fabrication quality which are facilitating advances in applications for electronic, magnetic and optical purposes. Part One reviews the key techniques involved in the epitaxial growth of complex metal oxides, including growth studies using reflec.